Atención al cliente en el comercial chino store en la ciudad de Babahoyo. - Saa Cabrera, Carlos Antonio (2024)
Customer service is of vital importance in any company, whether large or small, in order to achieve customer satisfaction and customer loyalty. During the analysis of this study, it was possible to obtain relevant data that allows us to know the deficiency of customer service, identifying significant problems such as the lack of efficient distribution of products, long waiting times and insufficient training of salespeople on the products they offer owns his company. These shortcomings were analyzed in depth using a specific research method (customer survey) in order to highlight the need and at the same time implement concrete improvements. In this case, after obtaining the results and their due analysis, the implementation of Key strategies on service quality includes a continuous training plan for salespeople on the products they offer in order to satisfy the needs and requests of customers, in addition to improving and minimizing waiting time during the process tension this will help customer retention.